کرونا وائرس کے مثبت سماجی پہلو:شریعت اسلامیہ کی روشنی میں تجزیاتی جائزہ : Positive Social Aspects of Corona Epidemic: An Analysis in the Light of Islamic Shariah - Fakhra Tahseen; Dr. Waleed Khan (Al Manhal Research Journal, 2024)
The present study attempts to bring forth positive social aspects of the Corona Virus induced epidemic of 2020-2021 in the light of Islamic Shariah. Islam is a complete and comprehensive religion that guides human beings on every aspect of this life and the life hereafter. Recently, the Novel Corona Virus that broke out in Wuhan, China in the late 2019 shook the world and brought death indiscriminately. Numerous challenges sprang out of it including religious, educational, economic, psychological, medical, and familial issues. On the contrary, this epidemic also taught us many positive values including simplicity, reticence, cleanliness, purity, social welfare, sacrifice, tolerance, and self-respect. It led us to value time and follow lofty objectives in life. It showed the possibility to kill social evils especially back biting, lying, prejudice, and jealousy. It emphasized on having a pure and helping family life. It taught us to follow the principles of nature with simplicity as the core value. The world learnt the value of covering face (using a veil) by wearing face mask. Above all, it brought man closer to Allah Almighty. However, once man controlled this virus and developed a vaccine by the will of Almighty, he reverted to his previous faulty routine again. The lesson learnt during the epidemic must have been exercised in normal times as well but this did not happen. This study is going to delve into the positive effects of Corona virus epidemic to see how can the positive values learnt and practiced during the epidemic days can be made a part of our normal life now as well. This research will use the qualitative approach for analysis.